1990
DOI: 10.1123/pes.2.4.349
|View full text |Cite
|
Sign up to set email alerts
|

Peak Oxygen Uptake and Physical Activity in 11- to 16-Year-Olds

Abstract: The present study examined the relationship between peak V̇O2 and habitual physical activity in 11- to 16-year-old students. The peak V̇O2 of 111 girls and 85 boys was determined using treadmill or cycle ergometry. Habitual physical activity was estimated from minute-by-minute heart rate monitoring over three 12-hr periods during normal school days. Over half of the girls and one third of the boys failed to sustain a single 10-min period with their heart rate at or above 140 bpm. Only one boy sustained a daily… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
2
2

Year Published

1996
1996
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(24 citation statements)
references
References 0 publications
2
18
2
2
Order By: Relevance
“…The latter disciplines do state that most active play occurs outdoors in both genders (e.g., Sallis et al, 1990;Baranowski et al, 1993) and that # children B3 years or older (and adolescents) are more active than~children and adolescents of the same age (e.g., Armstrong et al, 1990Armstrong et al, , 1991Sallis et al, 1996;Beunen and Thomis, 1999;Bradley et al, 2000). In general, they also find ethnic and socioeconomic ''effects'' in active physical activity (e.g., Sallis et al, 1996), similar to our attributes classes.…”
supporting
confidence: 77%
“…The latter disciplines do state that most active play occurs outdoors in both genders (e.g., Sallis et al, 1990;Baranowski et al, 1993) and that # children B3 years or older (and adolescents) are more active than~children and adolescents of the same age (e.g., Armstrong et al, 1990Armstrong et al, , 1991Sallis et al, 1996;Beunen and Thomis, 1999;Bradley et al, 2000). In general, they also find ethnic and socioeconomic ''effects'' in active physical activity (e.g., Sallis et al, 1996), similar to our attributes classes.…”
supporting
confidence: 77%
“…In the present study physical activity was recorded for four days. Armstrong et al (1990) compared physical activity of children aged 11 to 16 years on week and weekend days and found no significant differences, in the present study it was logistically easier to visit children's homes during the weekends.…”
Section: Methodsmentioning
confidence: 92%
“…The system can be worn during all normal activities without altering usual physical activity patterns. Treiber et al (1989) have shown this method to have good validity in children aged 5 to 10 years and it has been widely used in physical activity surveys of young people (Armstrong et al, 1990;Atkins, 1998).…”
Section: Methodsmentioning
confidence: 99%
“…5,6 This focus is timely, as these fatness trends are accompanied by evidence of low levels of activity, particularly in girls. 7,8 Furthermore, the increasing prevalence of inactive leisure pursuits, such as watching television and playing computer games, is of concern as evidence is emerging, linking these activities directly to obesity. 9 Change in eating styles is also an important contributory factor to the increasing level of overweight and obesity.…”
Section: Introductionmentioning
confidence: 99%